卒中院前急救与血压管理的挑战与突破：从现状到未来（Challenges and Breakthroughs in Prehospital Emergency Care and Blood Pressure Management for Stroke: Current Status and Future Directions） - 陈晨，刘飞凤，熊昕丽，汤跃宇，李刚（CHEN Chen, LIU Feifeng1, XIONG Xinli, TANG Yueyu, LI Gang） (Zhongguo cuzhong zazhi, 2025)
卒中作为我国居民的首位死因，其急救效果高度依赖于超早期干预。然而，当前卒中的院前急救仍以识别和转运为主，缺乏针对性的治疗措施。血压管理是影响卒中患者预后的关键因素之一，但在卒中的院前急救中，血压管理因缺血性卒中与出血性卒中的病理机制存在差异而面临严峻挑战：缺血性卒中需维持脑灌注压以保护缺血半暗带，而出血性卒中需快速降压以抑制血肿扩大。最新研究证据提示，在缺乏卒中分型诊断时，院前强化降压[收缩压目标130～140 mmHg（1 mmHg=0.133 kPa）]未能改善卒中患者的预后，且对出血性卒中和缺血性卒中患者的预后影响呈现相反效果，这凸显了院前卒中分型诊断的重要性和紧迫性。目前尚缺乏低成本、便于推广的院前卒中分型诊断措施。本文就卒中院前血压管理和院前卒中分型诊断的现状及最新进展进行论述，以期为该领域未来的研究方向提供参考。Abstract: Stroke, as the leading cause of death among Chinese residents, has an emergency treatment effect highly dependent on ultra-early intervention. However, current prehospital emergency care for stroke mainly focuses on recognition and transportation, lacking targeted treatment measures. Blood pressure management is one of the key factors affecting the prognosis of stroke patients. Yet, in prehospital emergency care for stroke, blood pressure management faces significant challenges due to the different pathological mechanisms of ischemic stroke and hemorrhagic stroke: ischemic stroke needs to maintain cerebral perfusion pressure to protect the ischemic penumbra, while hemorrhagic stroke requires rapid blood pressure reduction to suppress hematoma expansion. The latest research evidence indicates that in the absence of stroke subtype diagnosis, prehospital intensive blood pressure reduction [with a systolic blood pressure target of 130-140 mmHg (1 mmHg=0.133 kPa)] not only fails to improve the prognosis of stroke patients but also exerts opposite effects on the prognosis of patients with hemorrhagic stroke and ischemic stroke, highlighting the critical importance and urgency of prehospital stroke subtype diagnosis. Currently, there is a lack of low-cost and easily implementable methods for prehospital stroke subtype diagnosis. This review summarizes the current status and recent advances in prehospital blood pressure management and stroke subtype diagnosis, aiming to provide references for future directions in this field.